Weeds in action: Vegetal political ecology of unwanted plants. (February 2022) - Argüelles, Lucía; March, Hug
This paper presents a vegetal political ecology of weeds. Weeds have barely been analysed in the burgeoning field of 'more-than-human' scholarship, this despite their ubiquity and considerable impact on human social life. We review how geographical scholarship has represented weeds' material and political status: mostly as invasive plants, annoying species in private gardens and spontaneous vegetation in urbanized landscapes. Then, bringing together weed science, agronomic science and the critical geography of agriculture, we show how weeds ecology, weeds management and the environmental problems which weeds are entangled have critically shaped the industrial agriculture paradigm. Three main arguments emerging from our analysis open up new research avenues: weeds' disruptive character might shape our understanding of human-plant relationships; human-weeds relation in agriculture have non-trivial socio-economic and political implications; and more-than-human approaches, such as vegetal political ecology, might challenge dominant modes of considering and practicing agriculture.